A multi-dimensional FBSDE with quadratic generator and its applications - Rotenstein Eduard (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica, 2015)
We consider, in the Markovian framework, a multi-dimensional forward - back - ward stochastic differential equation with quadratic growth for the generator function of the backward system. We prove an existence result of the solution and we use this result for pricing and hedging of contingent claims that depend on non-tradeable indexes by portfolios consisting in correlated risky assets.